Applicability of lipid ratios in the prediction of atherogenic risks of women on combined oral contraceptives in North-Central Nigeria - Olanrewaju Saheed Jimoh; Hidaayah Oluwamayowa Jimoh - Abdulghaffaar; Tola Yinka Bakare; Gbenga Omotade Popoola; Waliu Olatunbosun Oladosu; Elizabeth Oluwakemi Grillo; Abdullahi Ahmed; Abiodun S Adeniran (Wolters Kluwer Medknow Publications, 2023)
Background: Combined Oral Contraceptive (COC) pill is associated with atherogenic and cardiovascular changes. Some service providers use individual lipid parameters to assess these changes unlike objective calculation using standard formulae. Objective: To determine and compare the atherogenic changes in women on COCs using six lipid ratios; coronary heart disease risk ratio, atherogenic index of plasma, atherogenic co-efficient, Cholesterol index, Castelli risk index I, and Castelli risk index II. Materials and Methods: A prospective, comparative study among new acceptors of contraceptives at four family planning clinics in Ilorin, North-Central Nigeria. Participants were categorized into COCs acceptors (group I, n=120) and acceptors of non-hormonal contraceptives (group II, n=120). Participants were followed up with serial lipid profiles at 0, 3 and 6 months after uptake. Atherogenic risks were calculated using six standard formulae; statistical analysis was with SPSS version 21.0 and Analysis of variance (ANOVA) was used to compare the differences of more than two means, Bonferroni Post Hoc test was used to test for specific significance within the group and p-value <0.05 was considered significant. Results: A total of 225 participants (111 COC users, 114 non-COC users) aged 19 to 48 years completed the study. Serum levels of Low-Density Lipoprotein showed a statistically significant rise among the COC users over the study period (p=0.038), especially between the third and sixth months. The lipid ratios were statistically increased using all six methods despite apparently normal lipid parameters. Conclusion: Atherogenic changes may occur in the presence of apparently normal lipid parameters among COC users; therefore, serial lipid ratio using standard method formulae is recommended.